Technology-related continuing professional development activities in supporting digital transformation in academic libraries in Uganda - Nakaziba, Sarah; Ngulube , Patrick (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: To survive and thrive in a technologically advanced academic setting, librarians working in academic libraries need to revamp their competencies and knowledge through technology-rated continuing professional development. Purpose: The purpose of this study was to examine the role of technology-related continuing professional development activities in enhancing digital transformation in selected Ugandan academic libraries. Method: A convergent parallel mixed methods design was used to collect qualitative and quantitative data from six universities in Uganda. Qualitative data were obtained from six University Librarians working in these universities, and quantitative data were collected from 76 librarians with a minimum degree-level qualification. Findings: The findings revealed that the librarians who had gained digital competencies from attending technology-related CPD activities had implemented or supported various digital transformations in their institutions. Thus, concluding that technology-related CPDs have a role in implementing digital competencies in academic libraries. Conclusion: The findings further revealed several challenges affecting the implementation of digital transformation, such as a lack of awareness of digital technologies, insufficient ICT infrastructure, limited staff, librarians’ failure to understand their changing roles, limited funding, absence of relevant policies or frameworks, and limited management support.